Strategi Pembelajaran PAI untuk Mengatasi Krisis Moral di Kalangan Remaja Era Digital - Nurul Hafidzah; Hayati Arifah Al-Bahri; Gusmaneli Gusmaneli (Jurnal Budi Pekerti Agama Islam, 2025)
The moral crisis affecting adolescents in the modern era poses a serious challenge to the world of education, particularly Islamic Religious Education (PAI). Phenomena such as declining morals, deviant behavior, and low moral awareness demonstrate the need for strategic efforts in developing adolescent character. This article aims to examine various PAI strategies in addressing the adolescent moral crisis, including strengthening religious values, implementing interactive and participatory learning methods, teacher role models (uswah hasanah), utilizing social media as a means of moral education, collaboration between schools and parents, and developing religious-based extracurricular activities. Through the implementation of these strategies, it is hoped that PAI learning can be more effective in instilling moral and spiritual values ​​in adolescents, thereby forming a generation with Islamic character, noble morals, and capable of facing the moral challenges of the digital era.